Diagnostic laparoscopy is underutilized in the staging of gastric adenocarcinoma regardless of hospital type: An US safety net collaborative analysis. Issue 4 (14th June 2022) - Leder Macek, Aleeza J.; Wang, Annie; Turgeon, Michael K.; Lee, Rachel M.; Russell, Maria C.; Porembka, Matthew R.; Alterio, Rodrigo; Ju, Michelle; Kronenfeld, Joshua; Goel, Neha; Datta, Jashodeep; Maker, Ajay V.; et al.
Abstract: Background: Diagnostic laparoscopy (DL) is a key component of staging for locally advanced gastric adenocarcinoma (GA). We hypothesized that utilization of DL varied between safety net (SNH) and affiliated tertiary referral centers (TRCs). Methods: Patients diagnosed with primary GA eligible for DL were identified from the US Safety Net Collaborative database (2012–2014). Clinicopathologic factors were analyzed for association with use of DL and findings on DL. Overall survival (OS) was analyzed by Kaplan–Meier method. Results: Among 233 eligible patients, 69 (30%) received DL, of which 24 (35%) were positive for metastatic disease. Forty percent of eligible SNH patients underwent DL compared to 21.5% at TRCs. Lack of insurance was significantly associated with decreased use of DL (OR 0.48,   p  < 0.01), while African American (OR 6.87,   p  = 0.02) and Asian race (OR 3.12,   p  ≤ 0.01), signet ring cells on biopsy (OR 3.14,   p  < 0.01), and distal tumors (OR 1.62,   p  < 0.01) were associated with increased use. Median OS of patients with a negative DL was better than those without DL or a positive DL (not reached vs. 32 vs. 12 months, p  < 0.005, Figure 1). Conclusions: Results from DL are a strong predictor of OS in GA; however, the procedure is underutilized. Patients from racial minority groups were more likely to undergo DL, which likely accounts for higher DL rates among SNH patients.